Evaluation of cationite efficiency during extraction of heavy metal ions from diluted solutions - Gomelya, Nikolai; Ivanova, Veronika; Galimova, Valentina; Nosachova, Julia; Shabliy, Tatiana (Eastern-European Journal of Enterprise Technologies, 2017)
Ion exchange is one of the methods that has been successfully employed in industry for extracting heavy metals from wastewater. We conducted research into ion-exchange processes of extraction of heavy metal ions on the weak- and strong-acid cationites from distilled and tap water. Heavy metal ion concentration was less than 1 mg/dm3. We established that in all cases efficiency of water treatment decreased at a decrease in the starting concentration of a metal. The process took place regardless of the degree of saturation of cationites with the ions of heavy metals or hardness ions when extracting copper from water. It is proposed to apply filters with combined action. It was established that at a concentration of copper ions of 10-2 mkg/dm3, copper did not sorb even when using filters with combined action. It is shown that effectiveness of the extraction of copper depends on the volume of filtering load. The concentration of copper ions in water was reduced to 0.053 mg/dm3. It was established that lead ions are almost completely extracted on a strong-acid cationite at concentrations less than 0.1 mkg/dm3. When removing lead ions, the degree of extraction grew while lowering the starting concentration of ions. Residual concentrations were below a sensitivity limit of the method − 10-3 mkg/dm3 (10-9 g/dm3). The processes of regeneration of strong- and weak-acid cationite were explored. Regeneration should be conducted applying the 2M solution of hydrochloric acid. Lead ion desorption efficiency reaches 100 %. It was found that the desorption efficiency increases with a decrease in the mass of sorbed lead. The degree of copper ion desorption in some cases reaches about 90 %.